Transforming Towards Secure Global Trade for Customs Administrations Powered by Blockchain - Abunqira, Hussam (2020)
As part of the international trade supply chain, Customs authorities act as the gatekeeper protecting the society and the economy. The trade supply chain involves several participants each performs its task based on the documents that are provided by the other participant in the trade supply chain. For instance, the customs officials process the customs declaration submitted by the broker and then send the results to the next participant. The customs authorities need to perform an accurate risk assessment to ensure that protection of society and trade are not impacted. The verification and risk assessment are costly processes. The isolation between the participants in the trade supply chain impacts the efficiency of the current international trade supply model. In this work, a blockchain-based solution with a plugin to empower the solution with risk assessment capabilities is proposed. To build this solution, a proof of concept (PoC) approach is followed using the IBM Hyperledger fabric and Python programming language. The participants of this international trade process are identified. Then, the detailed process, activities, assets, transactions that are performed by each participant are analyzed. After that, a solution architecture is designed followed by building the smart contracts and building the PoC. This computational model ensures secure transactions, traceable transactions, and an immutable data communication model for better coordination among the entities along the supply chain. To further enhance the blockchain solution, two models are proposed to provide Customs authority with online risk assessment capabilities; distributed risk assessment method and a hybrid risk assessment method that consists of distributed and centralized risk assessment processes. The real data used in this work was obtained from Dubai Customs and contains shipment declaration applications. This labelled data is used to evaluate two models. The first method reported significant results that can provide classification with 83% in terms of accuracy. While, the accuracy in the extended work for the first method achieved a higher accuracy of 92%. This work addresses important issues related to security and risk assessment and provide powerful methods that complement the risk assessments performed at the customs authority by providing feedback from the early stage of risk analysis. كجزء من سلسلة توريد التجارة الدولية، تعمل سلطات الجمارك بمثابة حارس يحمي المجتمع والاقتصاد. تتضمن سلسلة التوريد التجارية عدة مشاركين يؤدون كل منهم مهمته بناءً على المستندات التي يقدمها المشارك الآخر في سلسلة التوريد التجارية. على سبيل المثال، يقوم موظفو الجمارك بمعالجة البيان الجمركي المقدم من قبل الوسيط ومن ثم إرسال النتائج إلى المشارك التالي. تحتاج السلطات الجمركية إلى إجراء تقييم دقيق للمخاطر لضمان عدم التأثير على حماية المجتمع والتجارة. تعتبر عمليات التحقق وتقييم المخاطر عمليات مكلفة على السلطات الجمركية. تؤثر العزلة بين المشاركين في سلسلة الإمداد التجاري على كفاءة نموذج الإمداد التجاري الدولي الحالي. في هذا العمل، يُقترح حل بالاعتماد على تقنية البلوك تشين ع مع مكون إضافي لتمكين الحل بقدرات تقييم المخاطر. لبناء هذا الحل، يتم اتباع نهج الدليل والنموذج التجريبي للمفهوم باستخدام نسيج اي بي ام هيبرلدجر ولغة البرمجة بايثون. تم تحديد المشاركين في عملية التجارة الدولية هذه. بعد ذلك، يتم تحليل تفاصيل العمليات والأنشطة والأصول والمعاملات التي يقوم بها كل مشارك في السلسلة. بعد ذلك، يتم تصميم هندسة الحلول متبوعة ببناء العقود الذكية وبناء النموذج التجريبي. يضمن هذا الحل المعاملات الآمنة والمعاملات التي يمكن تتبعها ونموذج اتصال البيانات غير القابل للتغيير لتحسين التنسيق بين الكيانات على طول سلسلة التوريد. لزيادة تعزيز حل البلوك تشين، تم بناء نموذجان لتزويد السلطات الجمركية بقدرات تقييم المخاطر بشكل آني؛ طريقة تقييم المخاطر الموزعة وطريقة تقييم المخاطر المختلطة التي تتكون من عمليات تقييم المخاطر الموزعة والمركزية. يتم استخدام هذه البيانات لتقييم أداء النموذجين المقترحين في هذا العمل. حققت الطريقة الأولى نتائج مهمة يمكن أن توفر تصنيفًا بنسبة 83٪ من حيث الدقة في المتوسط. بينما حققت الطريقة الثانية نتائج أفضل بدقة وصلت إلى 92٪. يتناول هذا العمل قضايا مهمة تتعلق بالأمن وتقييم المخاطر ويوفر طرقًا قوية تكمل تقييمات المخاطر التي يتم إجراؤها في مصلحة الجمارك من خلال توفير التغذية المرتدة من المرحلة المبكرة لتحليل المخاطر.